Predictive risk factors of steroid dependent nephrotic syndrome in children with idiopathic nephrotic syndrome - Ehsan Valavi; Azar Nickavar; Parisa Amoori; Mohsen Fathi; Bahareh Valavi (Journal of Nephropharmacology, 2023)
Introduction: Steroid dependent nephrotic syndrome (SDNS) is a difficult and troublesome presentation of idiopathic nephrotic syndrome (INS) in children, with complicated management and increased morbidity. Objectives: The aim of this study was to identify the predictive clinical and laboratory characteristics of patients with SDNS, for parents counseling, appropriate management and improving outcome. Patients and Methods: A total of 374 children with steroid sensitive INS were evaluated in two groups as steroid dependent (group 1=199) and non-steroid dependent (group 2= 175) INS. SDNS was defined as ≥2 relapses during steroid reducing treatment or 15 days after discontinuation of corticosteroids. Results: Mean age at presentation was significantly lower in children with SDNS than those without steroid dependency (P=0.022). Diagnostic age less than two years (P=0.016), total relapses (P<0.001), relapse/year (P<0.001), body mass index (BMI) (P=0.002) and serum cholesterol level (P=0.042) were significantly higher in children with SDNS, compared to those with low-frequent relapse. Mean relapse rate decreased significantly in SDNS with immunosuppressive treatment (P<0.001). Conclusion: Age younger than two years at diagnosis, high BMI, high relapse rate/year and hypercholesterolemia at remission are suggested as predictors of SDNS in children with INS.